Fake news detection using supervised machine learning techniques. Issue 1 (2nd January 2022) - Malhotra, Pooja; Malik, Sanjay Kumar
Abstract: As there are increasing wide variety of users on social media, information articles can be speedy posted or shared among customers without knowing its credibility and authenticity. Fast spreading of fake information articles, the use of unique social media structures can create inestimable damage to society. These actions should significantly jeopardize the reliability of information media systems. An efficient automated tool is the necessity to discover such misleading articles. We have done analysis to select the best algorithm which can classify the news article as a real news or fake news.